2017
DOI: 10.1016/j.neulet.2017.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Minor allele C of rs12807809 polymorphism in NRGN contributes to the severity of psychosis in patients with Schizophrenia in South Indian population

Abstract: Schizophrenia (SCZ) as a severe and complex neuropsychiatric disorder and is characterized by positive symptoms, negative symptoms and cognitive dysfunctions. Genome-wide association studies (GWAS) have identified a strong association between the single nucleotide polymorphism (SNP) rs12807809 upstream of Neurogranin (NRGN) in a European population. This evidence prompted us to conduct an association study among 1005 schizophrenia cases and 1069 controls in a South Indian Population using TaqMan Allelic discri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The genotypes of rs12807809 were confirmed by the Sanger sequencing technique. Large studies [3, 8, 30] found a low frequency of the CC genotype (less than 10% in both patients with SZ and HCs). In our study, the frequency of the CC genotype was 1.7% in patients with SZ and 12.1% in HCs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genotypes of rs12807809 were confirmed by the Sanger sequencing technique. Large studies [3, 8, 30] found a low frequency of the CC genotype (less than 10% in both patients with SZ and HCs). In our study, the frequency of the CC genotype was 1.7% in patients with SZ and 12.1% in HCs.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, in genome-wide association studies, a single nucleotide polymorphism (SNP), rs12807809, in the NRGN gene was reportedly associated with SZ [2], and the T allele conferred a high risk for SZ. An association of rs12807809 with SZ was also found in 1005 SZ patients and 1069 controls in a South Indian population; further analysis found a moderate association of rs12807809 with flat affect and hallucinations [3]. In addition, an expression quantitative trait loci (eQTL) analysis provided evidence for an increased risk for SZ with rs12807809 at a molecular level [4].…”
Section: Introductionmentioning
confidence: 99%
“…A genome-wide association study identified a relationship between schizophrenia and the single nucleotide polymorphism of rs12807809 in the NRGN ( Stefansson et al, 2009 ). In recent years, several reports attempted to reveal the association between rs12807809 polymorphism and schizophrenia among different populations, but the results were controversial ( Li et al, 2010 ; Sudesh et al, 2017 ). A recent meta-analysis aiming to integrate the present studies on the 12807809 polymorphism showed a statistically significant association between schizophrenia and rs12807809 polymorphism in the overall population in the allelic model (odds ratio = 1.10, 95% confidence interval 1.04–1.17).…”
Section: Associations Between Neurogranin and Neurological And Mentalmentioning
confidence: 99%